Control of articular synovitis for bone and cartilage regeneration in rheumatoid arthritis - Hiromu Ito; Furu Moritoshi; Motomu Hashimoto; Masao Tanaka; Shuichi Matsuda (BMC, 2018)
Abstract Background Rheumatoid arthritis is an autoimmune inflammatory disease, the specific feature of which is progressive joint destruction induced by synovitis. The universal consensus is that alleviation of the synovitis is essential to prevent joint destruction and achieve clinical remission. Main text We have shown that not only achieving but also maintaining remission is crucial to prevent the progression of joint destruction. Although regeneration of the damaged joints is considered very rare, accumulating evidence shows that it actually occurs in routine clinical practice as a result of strong inhibition of synovitis using highly potent medications. Oral and intravenous medications affect the whole body, but to promote joint regeneration in a particular joint, two potent options are intra-articular steroid injection and synovectomy. Conclusion In situations where strong inhibition of synovitis combined with self-regeneration cannot repair severe joint destruction, regenerative medicine may in the future play a crucial role in the regeneration of damaged joints.